Study Expression of Fibronectin in the Samples of Oral Squamous Cell Carcinoma - Zaidoon Jasim Rmaidh (Journal of Global Pharma Technology, 2019)
The current study included samples of 30 sample oral squamous cell carcinoma with a ranged age 33-67 years in mean age 47±9 in different sex.  Regarding the size of oral squamous carcinomacase, 10 cases of each size T1, T2 and T3 appeared in the same percentage (33.3%). Concerning grade of oral squamous cell carcinoma case, majority of them (15) cases (50%) had grade I, while (10) cases (33.3%) had grade II (oral squamous carcinoma well differentiated), (3) cases (10.0%) had grade III and (2) cases (7.1%) had grade IV (differentiated poorly oral squamous carcinoma).The results of analysis showed Positive fibrnectin expression using Immuno staining teqnique was found in all oral squamous cell carcinoma cases as brown extracellular matrix, cellular localization expression and cytoplasmic expression, fibrnectin expression using immunohistochemichal staining of the oral squamous carcinoma cases  which reveals that (5) cases (17.3%) showed  protein expression weak positive, (15) cases (50%) showed protein expression moderate positive and (10) cases (33.3%)showed  protein expression strong positive.Keywords: Fibronectin, Squamous carcinoma in oral, Immunohistochemichal teqnique.